2015
DOI: 10.1007/s12011-015-0383-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Supplementation With and Without Docosahexaenoic Acid on the Cardiovascular Disease Risk Based on Paraoxonase-1, hs-CRP, and ApoB/ApoA-I Ratio in Women with Iron Deficiency Anemia

Abstract: Numerous studies have demonstrated that tissue deposition of iron following prolonged high dose of oral supplementation for treatment of iron deficiency anemia (IDA) leads to body iron overload and oxidative stress, which starts the process of atherosclerosis. This study aimed to determine the effect of iron supplementation in combination with docosahexaenoic acid (DHA) on the cardiovascular disease risk based on paraoxonase-1 (PON-1), high-sensitivity C-reactive protein (hs-CRP), and ApoB/ApoA-I ratio in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In that study, Burillo et al reported that the supplement increased PON1 protein, thereby suggesting a positive change in the functionality of the HDL molecule [86]. Contrary to these findings, in a randomized controlled trial, women with iron deficiency anemia randomly assigned to receive 500 mg of DHA supplement or placebo with an iron tablet, once daily for 12 weeks, showed no significant differences in terms of serum PON1 concentration [87]. Four years ago, Whelan et al reviewed the effect of stearidonic acid, a highly unsaturated (n-3) PUFA that is effectively metabolized to eicopentaenoic acid, and concluded that its administration is a favorable modulator of PON1 [88].…”
Section: Dietary Lipidsmentioning
confidence: 99%
“…In that study, Burillo et al reported that the supplement increased PON1 protein, thereby suggesting a positive change in the functionality of the HDL molecule [86]. Contrary to these findings, in a randomized controlled trial, women with iron deficiency anemia randomly assigned to receive 500 mg of DHA supplement or placebo with an iron tablet, once daily for 12 weeks, showed no significant differences in terms of serum PON1 concentration [87]. Four years ago, Whelan et al reviewed the effect of stearidonic acid, a highly unsaturated (n-3) PUFA that is effectively metabolized to eicopentaenoic acid, and concluded that its administration is a favorable modulator of PON1 [88].…”
Section: Dietary Lipidsmentioning
confidence: 99%
“…Understanding the role of specific nutrients during inflammation and the body's response to dietary nutrient absorption in healthy, nutrient‐deprived, or inflamed conditions is essential for developing strategies to increase bioavailability of dietary nutrients in non‐communicable diseases through dietary means. In this paper, we explore the nutrient‐dependent acute immune response, with a focus on nutrients linked to inflammation and supported by double‐blind placebo‐controlled trials, such as iron, 30,31 vitamins A, 32 C, 33 and other antioxidants such as polyphenols 34…”
Section: Introductionmentioning
confidence: 99%